2007
DOI: 10.1590/s1679-62252007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Swimming performance of the migratory Neotropical fish Leporinus reinhardti (Characiformes: Anostomidae)

Abstract: The fishways built in Latin America were mainly based on those used in the northern hemisphere for passing salmonids upstream. However, the swimming capacity in terms of speed and endurance is a major factor concerning the design of a fishway, and this information is not available for migratory neotropical fish species. Therefore, studies on swimming performance of neotropical species is fundamental. The aim of this study was to estimate the critical, sustained and prolonged speeds for the piau-três-pintas Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 18 publications
0
35
1
5
Order By: Relevance
“…Leporinus elongatus is faster than Prochilodus lineatus; it had a lower mean ascent time (1.39 hours) than P. lineatus (3.76 hours), which required a longer time to pass through the fish ladder. According to Santos et al (2007), the swimming capacity of the piau (Leporinus reinhardti) explained the success of this genus in ascending fishways in Brazil. It is possible that the swimming capacity of this genus is greater than that of other migratory characiformes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leporinus elongatus is faster than Prochilodus lineatus; it had a lower mean ascent time (1.39 hours) than P. lineatus (3.76 hours), which required a longer time to pass through the fish ladder. According to Santos et al (2007), the swimming capacity of the piau (Leporinus reinhardti) explained the success of this genus in ascending fishways in Brazil. It is possible that the swimming capacity of this genus is greater than that of other migratory characiformes.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of the swimming performance of these species have been conducted only recently, and this information is available for two migratory species: Leporinus reinhardti (Characidae) and Pimelodus maculatus (Pimelodidae) (Santos et al, 2007;2008). Furthermore, information on the functional relationships associated with morphology and with behavior in fish passages remains scarce.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hoffman & Dunham (2007), the ability of fish to pass through culverts is affected by behavioral and physiological factors and by the physical conditions created by culverts. Studies carried out with Pimelodus maculatus (Siluriformes) showed that this species swims slower (Santos et al, 2006) than species of Characiformes, in the case of species considered as migratory, such as Leporinus reinhardti (Anostomidade) (Santos et al, 2007), and small-sized species, such as Bryconamericus stramineus (Characidae) (Castro et al, 2010). These characteristics can improve the Characiformes' ability to transpose obstacles, such as high water flows, which are frequently found in culverts.…”
Section: Discussionmentioning
confidence: 99%
“…Beach, 1984;Zou, 1982;Videler, 1993;Keynard, 1993). Critical velocities have been estimated for non salmonid species inhabiting northern hemisphere (Pavlov, 1989) but swimming capabilities for neotropical species are still scant (de Castro et al, 2010;Santos et al, 2007Santos et al, , 2009. Most neotropical fishes are smaller than salmonids but compensate by displaying higher metabolic rates as they inhabit warmer rivers.…”
Section: Discussionmentioning
confidence: 99%